Isolation of cellulose fibers from banana leaves - Premanarayani Menon, Narayanan Nair (Universiti Malaysia Sarawak (UNIMAS), 2013)
Banana leaves are one of the abundant agricultural wastes from banana plants cultivation. Thus, isolation of cellulose from banana leaves aims to reduce the waste production. Celluloses have received tremendous attention due to its potential application as reinforcing agent. Cellulose fibers from banana leaves have been isolated and characterized by FTIR and SEM. Banana fibers were treated with acidified sodium chlorite (NaClO2) and sodium hydroxide (NaOH) to remove lignin and hemicellulose respectively. The chemical treatment was subjected under different conditions, to study the effects of concentration, reaction duration on the removal of lignin and hemicellulose as well as on the surface morphology of the resultant cellulose fibers. Treatment of sample with 10 wt% of NaClO2 for 3 hours and 10 wt% of NaOH for 3 hours is the optimum conditions obtained from the study. Furthermore, the morphology of the isolated cellulose was studied across different ultrasonication time. The increase in ultrasonication time from 30 seconds to 240 seconds has resulted in the reduction of the diameter of cellulose fibers.